2019
DOI: 10.1039/c8cy02274g
|View full text |Cite
|
Sign up to set email alerts
|

Selenium reagents as catalysts

Abstract: Organoselenium chemistry is now become an important tool in synthetic and medicinal chemistry. Organoselenium reagents are more commonly known as electrophiles but there are few organic transformations where they act as nucleophiles. These reagents have been successfully employed to achieve number of synthetically important transformations such as oxyselenenylations, selenocyclisation and selenoxide eliminations etc. In past two decades, another episode of their success is introduced as they have developed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(63 citation statements)
references
References 178 publications
0
61
0
2
Order By: Relevance
“…Indeed, although selenium and its oxidised species were reported to show toxic effect at high concentrations, 78 growing attention is recently being paid to organoselenides catalysing organic reactions in environmentally friendly conditions. 79 In particular, this holds true when aqueous medium is considered. 80 In this context, good water solubility was achieved for 1-H and 1-CF 3 , since the compounds were prepared as hydrochloride salts.…”
Section: Oxidation By H 2 O 2 : Nmr Resultsmentioning
confidence: 96%
“…Indeed, although selenium and its oxidised species were reported to show toxic effect at high concentrations, 78 growing attention is recently being paid to organoselenides catalysing organic reactions in environmentally friendly conditions. 79 In particular, this holds true when aqueous medium is considered. 80 In this context, good water solubility was achieved for 1-H and 1-CF 3 , since the compounds were prepared as hydrochloride salts.…”
Section: Oxidation By H 2 O 2 : Nmr Resultsmentioning
confidence: 96%
“…Selenium-based catalysts have played an important role in organic synthesis, including carbon-carbon bond formations and oxidation reactions under relatively mild reaction conditions. [22,23,24] One reason of this extraordinary substrate scope is the ability that selenium in exhibiting variable oxidation states; in consequence, the selenium atom can easily increase the number of bond plus lone pairs, greater than that allowed by the Lewis octet rule. This tolerance for hypervalency facilitates a nucleophilic attack on selenium, and its larger size results in a better leaving group.…”
Section: Selenium-catalyzed Organic Reactionsmentioning
confidence: 99%
“…The versatile reactivity of selenium species provides eco‐friendly reaction conditions, functional compatibility and high atom economy [18,19,20,21] . Because of these features, the application of organoselenium compounds is not restrict to pharmacological studies, but also on selenium‐catalyzed reactions [22,23,24] . In an attempt to obtain more information regarding the selenium reactivity, organic chemists have considered the similarity of the properties of sulfur compounds with their selenium analogs, identifying useful characteristics of the selenium [25] .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of organoselenium compounds is linked to their synthetic applications as catalysts [ 1 , 2 , 3 , 4 ] and building blocks [ 5 , 6 , 7 , 8 , 9 ], allowing for several chemo-, regio- and stereoselective transformations [ 10 , 11 , 12 , 13 , 14 , 15 ]. Although organoselenium compounds have not yet reached the pharmacy shelves, studies in vitro and in vivo have demonstrated their effectiveness against several disorders [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%